2012
DOI: 10.1634/theoncologist.2011-0270
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Role of PET–CT in Staging Early Breast Cancer

Abstract: Introduction. Currently, there is a lack of data on the role of combined positron emission tomography-computed tomography (PET-CT) in the staging of early invasive primary breast cancer. We therefore evaluated the role of 18 F-fluorodeoxyglucose ( 18 F-FDG)-PET-CT in this patient population.Methods. We prospectively recruited 70 consecutive patients (69 women, one man; mean age, 61.9 ؎ 8.1 years) with early primary breast cancer for staging with 18 F-FDG-PET-CT. All PET-CT images were interpreted by two reader… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 40 publications
1
33
0
Order By: Relevance
“…Garami et al conducted one of the few studies of a possible role for FDG PET/CT in evaluation of tumor extension, and reported that the PET/CT sensitivity in terms of detection of multifocality was significantly higher than those of the traditional diagnostic modalities as US and mammography, by 100% and 43.8%, respectively (11). In another study, PET/CT revealed previously unsuspected multifocal disease in seven of 70 patients (12). Our results emphasize that PET/CT affords a higher specificity, PPV, and accuracy, compared to DCE-MRI, when used to detect multifocal disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Garami et al conducted one of the few studies of a possible role for FDG PET/CT in evaluation of tumor extension, and reported that the PET/CT sensitivity in terms of detection of multifocality was significantly higher than those of the traditional diagnostic modalities as US and mammography, by 100% and 43.8%, respectively (11). In another study, PET/CT revealed previously unsuspected multifocal disease in seven of 70 patients (12). Our results emphasize that PET/CT affords a higher specificity, PPV, and accuracy, compared to DCE-MRI, when used to detect multifocal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Further, selective SNB scheduling based on FDG PET/ CT imaging data might enhance the accuracy of SNB results and reduce the number of unnecessary invasive procedures (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, our team's limited experience and familiarity with PET probe-guided surgery may have influenced our outcomes. However, our findings highlight the importance of a recent call for a randomized, controlled trial to further investigate the role of PET/CT in breast cancer staging (39).…”
Section: Figure 2 Maximum Intensity Projection Of Positron-emission mentioning
confidence: 69%
“…At the present time, the role of FDG-PET imaging for regional breast cancer staging is quite limited: the spatial resolution of traditional FDG-PET is considered inadequate for assessing primary tumor size (1), and FDG-PET is not currently considered a viable substitute for sentinel lymph node sampling to evaluate for axillary nodal involvement (10). However, recent studies have suggested that FDG-PET may be of value in treatment planning by revealing otherwise undiagnosed multifocal disease (11), and one recent series showed that FDG-PET assessed lesion multifocality better than MRI (12). With increasing spatial resolution, FDG-PET may be incorporated in the future into risk stratification models that include, among other variables, estimates of the number of pathologic lymph nodes at the time of diagnosis (13).…”
Section: Discussionmentioning
confidence: 99%